(untitled) (Annals of Medical Research, 2021)
Aim: The excision repair cross-complementation group 1 (ERCC-1) protein is a potential prognostic biomarker of the efficacy of platinum-based chemotherapy in non–small-cell lung cancer (NSCLC). The purpose of this study was to evaluate the clinicopathology and prognostic significance of ERCC-1 expression, ERCC-1 (19q13) amplification in NSCLC patients; and the relationship between platinum-based chemotherapy. Materials and Methods: We used the ERCC-1 antibody to measure the level of expression of ERCC-1 protein by immunohistochemical analysis from 351 patients and ERCC-1 gene copy number was evaluated by fluorescence in situ hybridization (FISH) in tumors from 81 patients. Results: ERCC-1 expression in tumor cells was positive in 312 patients (88.9%). The ERCC-1 amplification in tumor cells was positive in 58 patients (71.6%) out of 81. The ERCC-1 amplification was also more frequent in early-stage tumors than late-stage tumors (p = 0.025). In the patients with positive ERCC-1 expression, longer overall survival was associated with early stage NSCLC (p =0.001). Patients having adenocarcinoma with negative ERCC-1 expression demonstrated longer overall survival than patients with squamous cell carcinoma (p = 0.037). Conclusion: Our study demonstrated that increased ERCC-1 amplification is not associated with ERCC-1 protein expression. High ERCC-1 expression in patients with early-stage NSCLC is a good prognostic factor, although it is a negative predictor, indicating treatment resistance, in patients with advanced-stage NSCLC receiving platinum-based chemotherapy. We suggest that patients having adenocarcinoma with negative ERCC-1 expression benefit more with platinum-based chemotherapies.